Electronic structure and superconductivity of FeSe-related superconductors. (16th April 2015) - Liu, Xu; Zhao, Lin; He, Shaolong; He, Junfeng; Liu, Defa; Mou, Daixiang; Shen, Bing; Hu, Yong; Huang, Jianwei; Zhou, X J
Abstract: FeSe superconductors and their related systems have attracted much attention in the study of iron-based superconductors owing to their simple crystal structure and peculiar electronic and physical properties. The bulk FeSe superconductor has a superconducting transition temperature ( T c ) of ∼8 K and it can be dramatically enhanced to 37 K at high pressure. On the other hand, its cousin system, FeTe, possesses a unique antiferromagnetic ground state but is non-superconducting. Substitution of Se with Te in the FeSe superconductor results in an enhancement of T c up to 14.5 K and superconductivity can persist over a large composition range in the Fe(Se, Te) system. Intercalation of the FeSe superconductor leads to the discovery of the A x Fe2− y Se2 (A = K, Cs and Tl) system that exhibits a T c higher than 30 K and a unique electronic structure of the superconducting phase. A recent report of possible high temperature superconductivity in single-layer FeSe/SrTiO3 films with a T c above 65 K has generated much excitement in the community. This pioneering work opens a door for interface superconductivity to explore for high T c superconductors. The distinct electronic structure and superconducting gap, layer-dependent behavior and insulator–superconductor transition of the FeSe/SrTiO3 films provide critical information in understanding the superconductivity mechanism of iron-based superconductors. In this paper, we present a brief review of the investigation of the electronic structure and superconductivity of the FeSe superconductor and related systems, with a particular focus on the FeSe films.